A qualitative examination of mothers' experiences in an interpersonal violence intervention initiative - Andrews, Naomi C. Z. (Journal of family violence, 2024)
Purpose: Interventions focused on women – and mothers, in particular – who have experienced violence in relationships are critical to supporting both mothers and their children. Existing evaluation research on such interventions focuses almost exclusively on outcome evaluation. Yet, these interventions are often multifaceted, requiring strong theoretical foundations, systemic changes, and capacity building for stakeholders at multiple levels. The goal of the current study was to describe critical intervention and implementation factors associated with an interpersonal violence intervention for mothers in communities across Canada, by understanding mothers’ experiences in the intervention. Method: Participants (N = 43, M = 30.14 years) were mothers in 11 different community-based projects. Participants completed interviews or focus groups following participation in a 6–8 week intervention, wherein they were asked open-ended questions about their experiences in the intervention. Results: Using a phenomenological approach, five key themes emerged as being particularly impactful to mothers’ experiences in the intervention: readiness, group content, group structure, group characteristics, and the broader structure of the community-based projects. Conclusion: Themes mapped onto the overarching theoretical frameworks from which the intervention is based: supporting relationships, building safety, and leveraging the existing capacities of community-based organizations that serve vulnerable families. Results highlight aspects of the intervention and experience that emerged as important to those experiencing violence in relationships.